Search
Ask a question
0

-2(r+6)=r-18

l need to understand how to figure this problem out

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Joanna B. | Math, Science, English TutorMath, Science, English Tutor
5.0 5.0 (334 lesson ratings) (334)
0

First, I would distribute the -2 to get -2r - 12 = r - 18.

Then get all the terms with variables to the same side by adding 2r to both sides.

-2r - 12 + 2r = r - 18 + 2r

This simplifies to -12 = 3r - 18.

Now add 18 to both sides to get all the constant terms on the same side.

-12 + 18 = 3r - 18 + 18

This simplifies to 6 = 3r.

To finish solving for r, divide both sides by 3.

6/3 = 3r/3.

This simplifies to 2 = r.